Developmental and lifelong dioxin exposure induces measurable changes in cardiac structure and function in adulthood - de Gannes , Matthew (Sci Rep, 2021)
Congenital heart disease (CHD) is the most common congenital abnormality. A precise etiology for CHD remains elusive, but likely results from interactions between genetic and environmental factors during development, when the heart adapts to physiological and pathophysiological conditions. Further, it has become clearer that early exposure to toxins that do not result in overt CHD may be associated with adverse cardiac outcomes that are not manifested until later life. Previously, interference with endogenous developmental functions of the aryl hydrocarbon receptor (AHR), either by gene ablation or by in utero exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a potent AHR ligand, was shown to cause structural, molecular and functional cardiac abnormalities and altered heart physiology in mouse embryos. Here, we show that continuous exposure to TCDD from fertilization throughout adulthood caused male mice to underperform at exercise tolerance tests compared to their control and female counterparts, confirming previous observations of a sexually dimorphic phenotype. Renin-angiotensin stimulation by angiotensin II (Ang II) caused measurable increases in blood pressure and left ventricle mass, along with decreased end diastolic volume and preserved ejection fraction. Interestingly, TCDD exposure caused measurable reductions in the myocardial hypertrophic effects of Ang II, suggesting that endogenous AHR signaling present in adulthood may play a role in the pathogenesis of hypertrophy. Overall, the findings reported in this pilot study highlight the complex systems underlying TCDD exposure in the development of cardiac dysfunction in later life.